2013
DOI: 10.1109/tuffc.2013.2796
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the feasibility of acoustic radiation force impulse shear wave elasticity imaging of the uterine cervix with an intracavity array: a simulation study

Abstract: The uterine cervix softens, shortens, and dilates throughout pregnancy in response to progressive disorganization of its layered collagen microstructure. This process is an essential part of normal pregnancy, but premature changes are associated with preterm birth. Clinically, there are no reliable noninvasive methods to objectively measure cervical softening or assess cervical microstructure. The goal of these preliminary studies was to evaluate the feasibility of using an intracavity ultrasound array to gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 60 publications
(56 reference statements)
1
26
0
1
Order By: Relevance
“…Recently, researchers have begun using shearwave elastography to evaluate cervical tissue stiffness (for example, Hernandez-Andrade, 2014; Palmeri et al 2013) because of its advantage that the generation of the mechanical impulse is operator independent and the stiffness measurement is an absolute measurement. However, morphological factors can influence shear-wave propagation such as complex tissue composition and boundary condition.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, researchers have begun using shearwave elastography to evaluate cervical tissue stiffness (for example, Hernandez-Andrade, 2014; Palmeri et al 2013) because of its advantage that the generation of the mechanical impulse is operator independent and the stiffness measurement is an absolute measurement. However, morphological factors can influence shear-wave propagation such as complex tissue composition and boundary condition.…”
Section: Discussionmentioning
confidence: 99%
“…In our study of ultrasound attenuation assessment of human cervix tissue, ROI size was varied from 10.5 pulse length to The cervix is mainly composed of collagen with relatively few smooth muscle bundles. The alignment of collagen varies from one layer to another with inner and outer layer having collagen arranged longitudinally, however middle layer has circumferentially aligned collagen [15,41,42]. As the cervix remodels for birth the cervix softens before the cervical length decreases (after 30 weeks of gestation age) which happens along with change of collagen concentration [43].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that as the delivery time approaches the collagen rich cervix is filled with water and enzymes which results in a lower attenuation value and a softening of the cervix as it prepares for delivery [23][24][25]. Our earlier work showed that attenuation of the cervix decreased as the cervix prepared for delivery [8][9][10][11][12] while the softening of the cervix can also be quantified using shear wave elastography [13][14][15].…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Shear wave is monitored outside the region of excitation (ROE) within focal zone [17][18][19]. Many researchers have quantified tissue stiffness from shear wave speed (SWS) estimation from dynamic displacement data.…”
Section: Shear Wave Estimationmentioning
confidence: 99%